Walter Benjamin : An aesthetic of redemption - Wolin, Richard (Berkeley University of California Press, 1994)
Few twentieth-century thinkers have proven as influential as Walter Benjamin, the German-Jewish philosopher and cultural and literary critic. Richard Wolin's book remains among the clearest and most insightful introductions to Benjamin's writings, offering a philosophically rich exposition of his complex relationship to Adorno, Brecht, Jewish Messianism, and Western Marxism. Wolin provides nuanced interpretations of Benjamin's widely studied writings on Baudelaire, historiography, and art in the age of mechanical reproduction. In a new Introduction written especially for this edition, Wolin discusses the unfinished Arcades Project, as well as recent tendencies in the reception of Benjamin's work and the relevance of his ideas to contemporary debates about modernity and postmodernity.